Dmitriy Alexandrovich Yaremenko - «SISJP NAMS Ukraine», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
The article is dedicated to the memory of D. A. Yaremenko — a bright representative of the Sytenko’s orthopedic school, the carrier of its traditions.